Roles of public expenditures and public investments on the demand and productivity of agricultural inputs/services: Some insights from Nigeria - Takeshima, Hiroyuki; Edeh, Hyacinth O.; Andam, Kwaw S. (International Food Policy Research Institute, 2022)
Knowledge gaps remain as to how longer-term public investments (PI) such as agricultural research and development (R&D), and short-term interventions through other public expenditures in agriculture (PEA) complement each other in enhancing productivity and efficiency in the agrifood sector. This study attempts to partly fill this gap by using nationally representative panel household survey data, subnational PEA data, locations of national agricultural R&D, and various spatial agroclimatic data in Nigeria. The analyses generally indicate that marginal returns to agricultural inputs/services (fertilizer, agricultural mechanization, irrigation, extension, agricultural equipment, and family labor) often increase by PI that raise overall agroclimatic similarity (AS) (through R&D locations), as well as increase PEA-share by subnational governments. There is often complementarity between these PI and PEA, particularly for extension services, investment in agricultural equipment, irrigation, and in the northern part of the country. Promoting further adoptions of modern inputs/services, increasing PEA-share, and selecting PI for agricultural R&D given in-country variations in agroclimatic conditions can help raise agricultural profitability and incomes in Nigeria.